MODEL PEMBERDAYAAN HUKUM PEMBUDI DAYA IKAN MELALUI PENDEKATAN PENGEMBANGAN MODEL TRIPLE HELIX (STUDI DI KABUPATEN GRESIK) - Eny Sulistyowati; Muh. Ali Masnun; Mahendra Wardhana; Arinto Nugroho; Nurul Hikmah (Fakultas Hukum Universitas Tulang Bawang, 2021)
AbstractThe real contribution of fish farmer in the development of the national economy through the amount of fisheries production is not followed by the level of welfare of the fish farmer. That the welfare of fish farmers to be able to fulfill their needs with the income they obtain is still very limited. This article aims to analyze the legal empowerment model of fish farmer through the triple helix model development approach. This research is a sociolegal research which is a mixed method between legal research methods and social science. The data used are primary data and secondary data. The results showed that normatively, the role provisions of the government and fish breeders have been clearly regulated, but the provisions for tertiary institutions have not been regulated, even though the role played by universities is no less important. Higher education as one of the elements in the triple helix has human resources who are able to provide knowledge and understanding related to production sharing agreements through legal assistance and mentoring workshops. The government is responsible for the welfare of its citizens, not only acting as a regulator, but also as a facilitator, dynamist and catalyst. Keywords : Legal Empowerment, Fish Farmer,Triple Helix